2002
DOI: 10.4049/jimmunol.169.7.3978
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surfactant Proteins A, D, and C1q in the Clearance of Apoptotic Cells In Vivo and In Vitro: Calreticulin and CD91 as a Common Collectin Receptor Complex

Abstract: Removal of cells dying by apoptosis is essential to normal development, maintenance of tissue homeostasis, and resolution of inflammation. Surfactant protein A (SP-A) and surfactant protein D (SP-D) are high abundance pulmonary collectins recently implicated in apoptotic cell clearance in vitro. Other collectins, such as mannose-binding lectin and the collectin-like C1q, have been shown to bind to apoptotic cells and drive ingestion through interaction with calreticulin and CD91 on the phagocyte in vitro. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
405
3
6

Year Published

2003
2003
2006
2006

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 478 publications
(427 citation statements)
references
References 50 publications
10
405
3
6
Order By: Relevance
“…However, this leaves us with the obvious question, what kind of effector machinery does MBL utilize to remove apoptotic cells? Two recent studies have brought further insight to this question indicating that both C1q, SP-A, SP-D as well as MBL utilize the calreticulin/CD91 complex on phagocytes as acceptor site for sequestration of apoptotic material [9,16]. Consistent with these studies, we demonstrated that opsonization of apoptotic cells with MBL facilitated their uptake by macrophages.…”
Section: Discussionsupporting
confidence: 89%
“…However, this leaves us with the obvious question, what kind of effector machinery does MBL utilize to remove apoptotic cells? Two recent studies have brought further insight to this question indicating that both C1q, SP-A, SP-D as well as MBL utilize the calreticulin/CD91 complex on phagocytes as acceptor site for sequestration of apoptotic material [9,16]. Consistent with these studies, we demonstrated that opsonization of apoptotic cells with MBL facilitated their uptake by macrophages.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, heat shock proteins binding to CD91 19,20 may interfere with phagocytosis of apoptotic cells. [21][22][23] In such a model, the result of heat [5][6][7][8][9]. These mice, along with untreated naïve mice were rechallenged with 2 Â 10 6 parental CMT93 s.c., and tumor growth followed for 60 days.…”
Section: Discussionmentioning
confidence: 99%
“…Human alveolar macrophages were isolated by bronchoalveolar lavage from patients with Global Initiative for Global Initiative for Chronic Obstructive Lung Disease (GOLD) stage 2 COPD as described (31,45). The right middle lobe was lavaged with 100 ml of 0.9% saline solution at room temperature.…”
Section: Primary Cell Isolation and Culturementioning
confidence: 99%